2016
DOI: 10.1096/fj.201600927r
|View full text |Cite
|
Sign up to set email alerts
|

Serum stearic acid/palmitic acid ratio as a potential predictor of diabetes remission after Roux‐en‐Y gastric bypass in obesity

Abstract: Endogenous fatty acid metabolism that results in elongation and desaturation lipid products is thought to play a role in the development of type 2 diabetes mellitus (T2DM). In this study, we evaluated the potential of estimated elongase and desaturase activities for use as predictive markers for T2DM remission after Roux-en-Y gastric bypass (RYGB). The results of a targeted metabolomics approach from 2 independent studies were used to calculate 24 serum FA concentration ratios (product/precursor). Gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…Liquid chromatography coupled with mass spectrometry [ 7 , 11 , 13 , 25 , 30 32 , 41 44 , 48 , 50 , 51 ] and hydrogen nuclear magnetic resonance [ 11 , 26 , 33 , 35 , 37 40 , 45 47 , 49 ] were the most commonly used analytical platforms ( Figure 1 , Table 1 ). Gas chromatography was also a rather commonly used technique [ 7 , 27 , 28 , 34 37 , 42 , 44 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid chromatography coupled with mass spectrometry [ 7 , 11 , 13 , 25 , 30 32 , 41 44 , 48 , 50 , 51 ] and hydrogen nuclear magnetic resonance [ 11 , 26 , 33 , 35 , 37 40 , 45 47 , 49 ] were the most commonly used analytical platforms ( Figure 1 , Table 1 ). Gas chromatography was also a rather commonly used technique [ 7 , 27 , 28 , 34 37 , 42 , 44 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Serum (47%) [ 7 , 25 , 28 , 31 , 32 , 38 , 41 45 , 48 , 49 , 51 , 52 ] and plasma (25%) [ 11 , 27 , 30 , 33 , 34 , 37 ] were the most commonly used biological materials. Other analyzed samples were urine (12%) [ 13 , 26 , 37 , 39 ] and different types of tissues (16%)—heart [ 11 ], liver [ 40 , 45 ], or adipose tissue [ 28 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence accumulated to date has mainly focused on palmitic acid, with little attention being paid to stearic acid-induced worsening of β-cell function. In our previous studies and other research, it has been demonstrated that, whether in the postprandial serum of T2DM patients or in the fasting serum of highfat-diet-fed mice [1][2][3][4], only stearic acid levels were profoundly increased. Meanwhile, a long-term high level of stearic acid exhibited a stronger destructive effect on β cells than that of palmitic acid [2,5].…”
Section: Introductionmentioning
confidence: 77%
“…The prevalence of T2DM has been increasing worldwide, with an estimated 336 million people currently affected [21]. It is well established that exposing pancreatic β cells to an elevated level of stearic acid causes their dysfunction, which is far advanced by the time diabetes is diagnosed clinically [1][2][3]5]. Therefore, the optimal management and prevention of T2DM should aim to ameliorate β-cell dysfunction at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…It is irresponsible to judge the quality of a metabolite without dose. Citrulline is an important nutritional supplement to help balance nitrogen and metabolism in the body, whereas a previous study showed that increased plasma citrulline in obesity mice may predict the development of the metabolic syndrome . Although the visceral fat volume, plasma insulin and lipid concentrations of the xylitol‐fed rats were lower than those of the high‐fat diet rats , excessive xylitol could also lead to obesity and elevated blood lipids .…”
Section: Discussionmentioning
confidence: 98%